The Influence of Parenting Styles on Attachment Dynamics among Adult Couples - Bibi, Amna; Khatoon, Bibi Asma; Altaf, Nighat; Bukhari, Syeda Javaria (The Lighthouse Journal of Social Sciences, 2024)
The purpose of the current study is to find out the correlation between parenting styles, adult’s current attachment in intimate partners. The data (N= 250) was collected from District Haripur by applying purposive sampling technique. Correlational research design was applied to the current study. For measuring the study purpose, 2 scales were used, the first one is the Experiences in Close Relationships-Relationship Structures (ECR-RS) for measuring current attachments of individuals, and the second scale was the Parenting Styles and Dimensions Questionnaire to check 3 basic parenting styles. The statistical techniques applied for findings were descriptive statistics, Pearson correlation, t-test, and Annova. Present study reveals there is a significant relationship between parenting style, attachment styles. Finding reveals that anxious anxiety was higher in female while male suffer more avoidance anxiety. This study finding was highly scope-able in clinical psychology, educational psychology, counseling psychology, and in social psychology.